The Role of Structural Deterioration and Biomechanical Changes of the Necrotic Lesion in Collapse Mechanism of Osteonecrosis of the Femoral Head. Issue 5 (21st April 2022) - Wang, Peng; Wang, Cheng; Meng, Haoye; Liu, Guangbo; Li, Huo; Gao, Jianming; Tian, Hua; Peng, Jiang
Abstract : Osteonecrosis of the femoral head (ONFH) is a crippling disease which is due to a lack of effective therapeutic measures. Its natural progression is rapid, the internal bone structure of the femoral head changes dramatically, and the subsequent fractures and collapse cause severe hip pain and loss of hip function. Femoral head collapse is a critical turning point in the development of ONFH and is related to the prognosis of patients. Early prevention and intervention help to preserve the hip joint and delay femoral head collapse. However, the mechanism of collapse still needs to be further studied because it is affected by different complex factors. This review discusses the underlying causes of femoral head collapse from two aspects: structural degradation and regional changes of biomechanical properties in the necrotic femoral head. Abstract : Osteonecrosis is an ischemic disease in which local bone cells and bone marrow die, accompanied by the release of inflammatory factors and changes in the microenvironment. The repair process starts immediately, but abnormal repair process leads to structural changes of necrotic lesion. The structural degeneration of the femoral head, on the one hand, causes the decrease of mechanical properties and local stress concentration; on the other hand, it leads to the increase of contact stress. Reduced bearing capacity and abnormally distributed high stress promote the occurrence of subchondral fracture and femoral head collapse. In brief, the occurrence of collapse is the result of the combined effect of many factors.